2017
DOI: 10.1002/ppap.201600171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydroxyl radical formation in a gas‐liquid electrical discharge plasma reactor utilizing liquid and gaseous radical scavengers

Abstract: FIGURE 7 Discharge power, pH, and liquid conductivity after discharge, as well as H 2 O 2 concentration for both gas and liquid scavengers. The liquid and gas flow rates were 0.75 ml min −1 and 0.4 L min −1 . For the pure water cases the discharge power, pH, liquid conductivity after discharge, and H 2 O 2 concentration were 0.6 W, 5.2, 12 µS cm −1 , 9.1 × 10 −8 mol s −1 for gas, and 9.8 × 10 −8 mol s −1 for liquid HSIEH ET AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 85 publications
1
32
1
Order By: Relevance
“…These conclusions are supported by recent work with gas and liquid phase • OH scavengers. Experiments in the same flowing film reactor used in the present study, although with different power supply, have demonstrated that the total production rate of • OH is significantly higher than the amount which can be attributed to H 2 O 2 production alone . It was also found that a high concentration of • OH occurs throughout the plasma channel and not just at the plasma/liquid interface where the gradients in temperature and electron density are likely very steep and the H 2 O 2 is hypothesized to be formed.…”
Section: Resultsmentioning
confidence: 51%
“…These conclusions are supported by recent work with gas and liquid phase • OH scavengers. Experiments in the same flowing film reactor used in the present study, although with different power supply, have demonstrated that the total production rate of • OH is significantly higher than the amount which can be attributed to H 2 O 2 production alone . It was also found that a high concentration of • OH occurs throughout the plasma channel and not just at the plasma/liquid interface where the gradients in temperature and electron density are likely very steep and the H 2 O 2 is hypothesized to be formed.…”
Section: Resultsmentioning
confidence: 51%
“…H 2 O 2 can be formed through recombination reactions of OH radicals (R12) in the discharge region or gas‐liquid interface, and later diffuses into the liquid phase. The solubility of gas phase H 2 O 2 plays a major role in the existence of H 2 O 2 in liquid phase in the condition of plasma contacting the liquid or not‐contacting the liquid . In addition, due to dissolved oxygen in deionized water, H 2 O 2 can be generated by the recombination of HO 2 radicals (R13 and R14).…”
Section: Resultsmentioning
confidence: 99%
“…The electron is also hard to enter bulk liquid to dissociate H 2 O molecule as attached by water molecule . In the work by Hsieh et al with a liquid film discharge, it reported that H 2 O 2 is produced mostly near or in the plasma–liquid interface . In the work by Winter et al with Ar plasma jet, it reported that the solubility of gas phase H 2 O 2 plays a major role in generating H 2 O 2 in liquid.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few decades, increasing attention has been focused on atmospheric pressure plasma‐liquid systems (APP‐Ls), including their various applications, the physical and chemical processes of plasma–liquid interaction, and breakdown processes and mechanisms . APP‐Ls can be customarily divided into three categories according to the type of interactions with liquid: liquid phase discharges, discharges in gas phase with a liquid electrode, and bubble discharges.…”
Section: Introductionmentioning
confidence: 99%